Thrips (Insecta: Thysanoptera) from the Tama Abu Range, Sarawak - Yong Foo, Ng; A, Wells; A Mound, Laurence (Universitas Andalas, 2025)
Thrips, insects of the order Thysanoptera, play key roles as crop pests, pollinators across diverse plant families, predators of other arthropods, and contributors to forest ecosystem dynamics. Despite the high diversity of thrips in tropical regions, these areas remain insufficiently studied. A survey of thrips was conducted during the Tama Abu Scientific. A total of 46 species belonging to three families were collected. The majority (50%, or 23 species) of the collected species belonged to the family Thripidae. Aoratothrips tenuis Priesner (subfamily Panchaetothripinae) and Elaphrothrips sensitivus Priesner (subfamily Idolothripinae) had not been previously recorded from Malaysia. An annotated list of Thysanoptera collected is provided. This list is by no means exhaustive, as it is based on a limited collecting period; many further species can certainly be expected from the Tama Abu Range and its adjacent areas.